Photoelectron–photoion(s) coincidence studies of molecules of biological interest. Issue 37 (20th September 2022) - Bolognesi, P.; Avaldi, L.
Abstract : Photoelectron–photoion(s) coincidence, PEPICO, experiments with synchrotron radiation have become one of the most powerful tools to investigate dissociative photoionization thanks to their selectivity. Abstract : Photoelectron–photoion(s) coincidence, PEPICO, experiments with synchrotron radiation have become one of the most powerful tools to investigate dissociative photoionization thanks to their selectivity. In this paper their application to the study of molecular species of biological interest in the gas phase is reviewed. Some applications of PEPICO to the study of potential radiosensitizers, amino acids and small peptides and opportunities offered by the advent of novel methods for the production of beams of these molecules are discussed.